Composition of the Lithuanian Komsomol in June 1940–June 1941 - Maslauskienė , Nijolė (Genocidas ir rezistencija, 2016)
The Lithuanian Leninist Young Communist League (LLKJS) in Lithuania occupied by the Soviet Union was a political structure of the occupation regime, which provided a reserve and assistance to the ruling Communist Party and actively participated in the Sovietisation of the country and indoctrination of the youth in the spirit of Communism. In October 1940, the league was incorporated into the All-Union Leninist Young Communist League (VLKSM) and integrated to the USSR political system. Its aims were to extend the social base of the Communist Party, to exert political influence on youth, and to make the youth serve the occupation policy.With an aim of gaining social support and political influence among the youth, the Communist Party promoted the Komsomol. In summer 1940, fast and uncontrolled growth of its ranks was stimulated. In February 1941, LLKJS raised for itself a goal of making it into a massive organisation capable of embracing and exerting political control over youth. In order to improve the image of the Komsomol and to make its ethnic composition reflect that of Lithuania, joining the LLKJS was particularly promoted among workers, peasants, schoolchildren, Lithuanians, and Poles of Vilnius region.Between November 1940 and May 1941, a campaign of issuing the LLKJS certificates to its members took place, which was a cleansing campaign of the Komsomol on the basis of social and political criteria. This campaign was aimed at integrating the LLKJS into the VLKSM through the process of socio-political validation of its members and exclusion of those members, who were socially and politically hostile or unreliable to the occupation authorities. The campaign helped transform the LLKJS and make its composition similar to that of the VLKSM, and also make LLKJS a political structure, which complied with the needs of the occupation authorities and on which they could rely.Over a period of one year of the Soviet occupation, the ranks of the LLKJS increased 13-fold. Due to the political situation and wish to survive under the occupation, young people of various social groups and nationalities joined the LLKJS. Most of them chose cooperation with the Soviet regime and adaptation to its policies deliberately, others joined the ranks looking for employment or career opportunities, and yet others – seeking better learning conditions or being forced by other circumstances. Cleansing of the ranks of the Komsomol and regulation of its composition changed the social structure of the organisation. The majority of the members of the Komsomol were representatives of working class, peasants and Soviet officials who constituted the social backbone for the Communist Party. People of various nationalities joined the Komsomol. Initially, young people of certain ethnic groups, particularly Jews, actively joined the LLKJS. Later, in order to improve the image of the LLKJS and bring its ethnic composition to that of Lithuania, recruitment of Lithuanians into its ranks was particularly promoted.Although efforts were made for the LLKJS to grow, it did not become a mass organisation and its ranks remained sparse. It was a weak and non-influential political structure, unable to penetrate the youth and win them over. The attempts of the Komsomol to involve young people in the Sovietisation processes and to instil in them the Communist ideology was ineffective. Many young people were opposed to the occupation regime and its political structures. The spirit of opposition to the Soviet occupation was therefore active among the youth and resistance against it was imminent.
Keywords: Lithuania; Soviet occupation; communist party; collaborants